New species and redescriptions of mole crickets (Orthoptera: Gryllotalpidae: Gryllotalpinae) from Singapore, with key to Singaporean species - Tan, Ming Kai (Zootaxa, 2012)
Two new species of mole crickets of the genus Gryllotalpa from Singapore are described: Gryllotalpa nymphicussp. n and Gryllotalpa wallace sp. n. Gryllotalpa fulvipes Saussure, 1877 is redescribed. Key to the species of Gryllotalpa from Singapore is also provided.